The Contribution of Revista Estudos Feministas to Gender and Feminist Debates - Minella, Luzinete Simões (Revista Estudos Feministas, 2004)
This article proposes a reflection on the contribution of Revista Estudos Feministas (REF) to the gender and feminist debate, considering a synthesis of the texts issued in 1999 and 2000, the first two years of the period in which REF is being edited in Universidade Federal de Santa Catarina. This synthesis tries to identify the themes discussed by REF, verifying viewpoints, fields of knowledge, and methodological proceedings that have been used in the articles. The conclusion is that the set of contributions at issue, notwithstanding its epistemological diversity, reveals, at first, an accelerated absortion of new theoretical contributions, which tend to relativize those binary oppositions that supported the classical conception of science; secondly a permanent challenge of dogmatism; and finally, a continual reiteration of the force of social and historical processes, aiming at destabilize scientific paradigms.